Analysis of the bioethical principles that allow the National Policy to Fight Violence against Women (Research, Society and Development, 2020)
Violence against women has stimulated, over the years, many social mobilizations and the problem includes different expressions of violence, such as: domestic, sexual, physical, psychological, patrimonial, moral, institutional, among others, which demands of all society organized civil and government effective actions to combat it. Therefore, the work aimed to analyze the bioethical principles that permeate the National Policy to Combat Violence Against Women (PNEVCM). It is a documentary, exploratory and qualitative research. Data collection was carried out based on the PNEVCM structural document, available on the website of the National Secretariat for Policies for Women (SNPM). For the organization and treatment of the data, Bardin's content analysis was used. The data were allocated through the following topics: conceptual aspects of coping with violence; principles, guidelines and objectives of the PNEVCM and actions and priorities of the policy in question. In view of the study carried out, it was found that the National Policy to Combat Violence Against Women (PNEVCM) addresses, even if implicitly, the bioethical principles of beneficence, non-maleficence and justice or equity, explicitly bringing the principle of autonomy.